Learning and indigenous peoples during the pandemic: perspectives of and for Kalanguyans - Soriano, Randy F.; Camara, Jun S.; Salcedo, Renato E. (Journal of Education and Learning (EduLearn), 2025)
Through qualitative study and semi-structured interviews, the researchers explored the learning experiences of Kalanguyan teachers when schools were locked-down during the COVID-19 pandemic in Malico Elementary School, San Nicolas, Pangasinan Philippines. The results revealed the learning gaps, experiences, sacrifices, and challenges encountered by the pupils and teachers. Utilizing Colaizzi’s method, the themes generated from the interviews conducted were presented to the participants and field experts to confirm their validity and authenticity. The themes generated were the Knowledge gap in science, social science, numeracy, and reading, after-work teaching sacrifices outside the classroom, language being ‘fluid’ for kindergarten and grade school pupils, the ability of pupils being compromised during the pandemic, module no hero, no Kalanguyan is left behind, guidance from parents-plus and minus-is a source of active-passive support, uniting learning and culture through curriculum and programs, yes is the key to the workplace on and off pandemic, and assessing technology for Kalanguyans using culture as lens. The study also conducted strengths, weakness, opportunities, and threat (SWOT) analysis. The findings will serve as basis for extension activities which will be headed by Pangasinan State University and collaboration of Department of Education (DepEd) and stakeholders that encompasses range of activities aimed at supporting the community’s educational needs.